Symbiotic efficiency and compatibility of native rhizobia in northern Thailand with different soybean cultivars- II. Laboratory experiment using native isolates from irrigated soybean-growing areas - Shutsrirung A. (2014)
Symbiotic efficiency and compatibility of 81 isolates of native bradyrhizobia from irrigated areas in northern Thailand with four soybean cultivars and one cowpea cultivar were evaluated under laboratory conditions. Effectiveness and / or compatibility of the tested isolates were compared with those of a standard strain (Bradyrhizobium japonicum CB 1809) by using plants grown on plastic seed bags. Effectiveness of the isolates was also estimated using uninoculated control plants grown in a nitrogen-free solution. Nodulation of a wide range of host plants by the majority of the tested isolates was observed, which agreed well with the results of our previous field experiment (Shutsrirung et al. 2002: Soil Sci. Plant Nutr., 48, 491-499). Up to 75% of the tested isolates induced a higher growth efficiency than that of the uninoculated control in association with one of the tested cultivars, Black soybean. Comparision with uninoculated control plants, enable to estimate the proportion of the tested isolates leading to effective growth promotion (E + e) of each cultivar, namely, Black soybean (local Thai cultivar), 75%; Cowpea, 82%; SJ5 (commercial Thai cultivar), 33%; Bragg (US cultivar), 33%; and Improved Pelican (US cultivar), 9%. These results indicated that although isolates with a high infectiveness with both "Asian-type" and "US-type" soybeans could be found, a high frequency of isolates leading to inefficient nodules was observed in the US cultivar, suggesting the presence of genetic differences in the soybean cultivars that express high-preference (efficient nodules) or low-preference (inefficient nodules) for a certain group of tested isolates. Based on the results of this laboratory experiment together with our previous field experiment, native rhizobial populations in the irrigated area of northern Thailand could be separated into three groups; Group 1: rhizobium strains showing a high effectiveness with only Asian cultivars, Group 2: strains showing a high effectiveness with only US origin cultivars, and Group 3: strains showing a high effectiveness with both Asian and US origin cultivars. The majority of the native rhizobial populations belonged to Group 1. The isolates in Group 3 may display a high potential for manipulating useful rhizobial inoculant.